2007
DOI: 10.1590/s0100-39842007000600004
|View full text |Cite
|
Sign up to set email alerts
|

A importância da ultra-sonografia transvulvar na avaliação de parâmetros anatômicos relevantes no tratamento de mulheres com incontinência urinária de esforço

Abstract: OBJETIVO: Descrever a importância da ultra-sonografia transvulvar na avaliação das diferenças anatômicas induzidas pelas cirurgias de sling de fáscia lata e tension-free vaginal tape. MATERIAIS E MÉTODOS: Quarenta mulheres com incontinência urinária de esforço, com idades entre 30 e 60 anos, foram tratadas por sling de fáscia lata (20 pacientes) ou tension-free vaginal tape (20 pacientes). A ultra-sonografia transvulvar da junção uretrovesical e da uretra proximal foi a principal ferramenta de investigação pré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…However, regardless the cause of SUI, nowadays, there is some consensus also to measure urethral hypermobility 30 . Recently, ultrasound seems to play an important role in the study of the urethral vesical junction(UVJ) and the proximal urethra (PU), also because it is a simple, low-cost, innocent and easily repeatable technique 30,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, regardless the cause of SUI, nowadays, there is some consensus also to measure urethral hypermobility 30 . Recently, ultrasound seems to play an important role in the study of the urethral vesical junction(UVJ) and the proximal urethra (PU), also because it is a simple, low-cost, innocent and easily repeatable technique 30,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the urodynamic study can only indirectly demonstrate the vertical mobility of the urethrovesical junction (UVJ) and proximal urethra (PU). Differently, ultrasonography can demonstrate a real image, with positioning and mobility of the UVJ and PU (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography of the UVJ and PU has increasingly been used in the preoperative evaluation of patients with stress urinary incontinence as well as in their postoperative follow-up for defining topographic parameters regarding the UVJ and PU positioning according to the surgical technique utilized (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(17)(18)(19) . An original study demonstrates that the UVJ and PU positioning represents a good prognostic factor of the success or failure of the surgical correction of stress urinary incontinence (14) .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the urethrovesical junction (UVJ) and proximal urethra (PU) mobility in the maintenance of female urinary continence has already been established [4,[6][7][8][9][10][11] . However, the urodynamic evaluation determines only indirectly the UVJ and PU mobility, differently from what can be clearly demonstrated in real time imaging by ultrasound [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%
“…The ultrasonographic examination of the UVJ and PU has been increasingly used in the preoperative evaluation and postoperative follow-up of patients with SUI, to document the UVJ and PU positioning before and after the elected surgical treatment [4][5][6][7][8][9][10][11][12][13][17][18][19] . At least one study suggested that the positioning of the UVJ and PU in the postoperative period is a good marker for treatment prognosis (whether a surgical procedure for SUI correction had been successful or not) [14] .…”
mentioning
confidence: 99%